Thyroid hormone-induced expression of inflammatory cytokines interfere with resveratrol-induced anti-proliferation of oral cancer cells. (October 2019) - Chen, Yi-Ru; Chen, Yu-Shen; Chin, Yu-Tang; Li, Zi-Lin; Shih, Ya-Jung; Yang, Yu-Chen S.H.; ChangOu, Chun A.; Su, Po-Yu; Wang, Shwu-Huey; Wu, Yun-Hsuan; Chiu, Hsien-Chung; Lee, Sheng-Yang; et al.
Abstract: Thyroid hormone, L-thyroxine (T4 ), induces inflammatory genes expressions and promotes cancer growth. It also induces expression of the checkpoint programmed death-ligand 1 (PD-L1), which plays a vital role in cancer progression. On the other hand, resveratrol inhibits inflammatory genes expressions. Moreover, resveratrol increases nuclear inducible cyclooxygenase (COX)-2 accumulation, complexes with p53, and induces p53-dependent anti-proliferation. In this study, we investigated the effect of T4 on resveratrol-induced anti-proliferation in oral cancer. T4 increased the expression and cytoplasmic accumulation of PD-L1. Increased expressions of pro-inflammatory genes, interleukin ( IL ) -1β and transforming growth factor ( TGF ) -β1, were shown to stimulate PD-L1 expression. T4 stimulated pro-inflammatory and proliferative genes expressions, and oral cancer cells proliferation. In contrast, resveratrol inhibited those genes and activated anti-proliferative genes. T4 retained resveratrol-induced COX-2 in cytoplasm and prevented COX-2 nuclear accumulation when resveratrol treated cancer cells. A specific signal transducer and activator of transcription 3 (STAT3) inhibitor, S31-201, blocked T4 -induced inhibition and restored resveratrol-induced nuclear COX-2 accumulation. By inhibiting the T4 -activated STAT3 signal transduction axis with S31-201, resveratrol was able to sequentially reestablish COX-2/p53-dependent gene expressions and anti-proliferation. These findings provide a novel understanding of the inhibitory effects of T4 on resveratrol-induced anticancer properties via the sequential expression of PD-L1 and inflammatory genes.